If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + 5 = 2b + -8 Reorder the terms: 5 + 6b = 2b + -8 Reorder the terms: 5 + 6b = -8 + 2b Solving 5 + 6b = -8 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 5 + 6b + -2b = -8 + 2b + -2b Combine like terms: 6b + -2b = 4b 5 + 4b = -8 + 2b + -2b Combine like terms: 2b + -2b = 0 5 + 4b = -8 + 0 5 + 4b = -8 Add '-5' to each side of the equation. 5 + -5 + 4b = -8 + -5 Combine like terms: 5 + -5 = 0 0 + 4b = -8 + -5 4b = -8 + -5 Combine like terms: -8 + -5 = -13 4b = -13 Divide each side by '4'. b = -3.25 Simplifying b = -3.25
| q=p-4 | | ((3x^2)+1)(3x-2)=0 | | q=50-0.5p | | 2w-2xw=332 | | ((2x^2)+1)-(3x-2)=0 | | (X+2)-X=60 | | (2x^2)-(3x-2)=0 | | 6+3x-2y=0 | | 9x^2/5 | | 4x^3-16x^2+15x+2=0 | | 4x^3-16x+15x+2=0 | | y^2x^2+xsiny=4 | | 5x+4=20x-4 | | y=2x^4+8x^3+4x^2-8x | | -6h+4-1+h=11 | | 6+8+(-8)= | | -6/11/(-3)= | | 5+4[3(x-4)+6]=5-6(x+9)-6 | | x^2+35=15 | | Isb+5= | | -1/9/(-8)= | | 3g-19+11g-21= | | (-7^2a^3b/b^3)^-1 | | -37/37 | | -3/4/4= | | 14/(-2/7)= | | -1/(-6/5)= | | -32/(-2)= | | -2/3(-21)= | | -1/2(28)= | | (-16)^-3/4 | | 2/15=w/65 |